Structural changes of hydroxyapatite coating electrophoretically deposited on NiTi shape memory alloy. Issue 10 (July 2018) - Dudek, Karolina; Dulski, Mateusz; Goryczka, Tomasz; Gerle, Anna
Abstract: The surface of the NiTi shape memory alloy was functionalized through the deposition of hydroxyapatite (HAp) coatings using the electrophoretic method (EPD). The electrophoresis carried out at the voltage of 40 V during the time of 120 s did not affect the crystalline structure of the initial HAp powder and, at the same time, ensured obtaining a homogeneous layer without visible cracks or discontinuities. Next, the coatings were subjected to heat treatment at 800 °C for 2 h in vacuum, wherein the applied conditions did not affect the decomposition of the deposited hydroxyapatite. The heat treatment resulted in the formation of carbonate apatite (C-HAp) in the HAp layer and in ceramic particles' coalescence. Changes in the morphology and roughness of the layer as well as partial decomposition of the NiTi substrate parent phase into Ti2 Ni and Ni4 Ti3 phases were also observed.